The role of today's museum - Gray, Clive; McCall, Vikki (New York : Routledge, 2020)
"The Role of Today's Museum provides a thorough investigation of what museums do and why. Arguing that museums are multi-functional institutions, the book examines the consequences of this for the services that museums provide, the publics to whom they are provided and the providers themselves. Adopting a wide perspective on understandings of the roles of museums and considering the different environments within which museums operate, Gray and McCall provide a new perspective on how transformations, as well as the gaps between intended policies and the actual work that is undertaken within museums, can be both identified and understood. By differentiating between social, economic and political visions and expectations of museums, the analysis in this book allows for a fuller understanding of what these organisations do and provide for their societies and the struggles and negotiations that surround their existence. The Role of Today's Museum takes a critical, interdisciplinary approach to studying museums and museum policy. As a result, the book will be of interest to academics and students engaged in the study of museums, cultural policy, social policy, cultural sociology, public policy and cultural and political economy. Highlighting the gaps that exist between policy ideals and museum practices, the book also provides valuable insights to policymakers and practitioners"--
OCLC-licensed vendor bibliographic record.
Keywords: Museums -- Textbooks; POLITICAL SCIENCE / Public Policy / Cultural Policy